Public investments and poverty reduction - Dorosh, Paul A.; Thurlow, James; Kebede, Frehiwot Worku; Ferede, Tadele; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2020)
Chapter 13, “Public Investments and Poverty Reduction,” presents results of general equilibrium simulations of the impacts of alternative investment strategies, focusing on national income (GDP) and incomes of the poorest 40 percent of the population in both rural and urban areas. These simulations, which incorporate the major factors discussed in this book—including land constraints, productivity growth, migration, expanding markets, rising incomes and consumption, and greater urbanization—show that although urban investments generate faster economic growth and structural transformation, investments in the rural economy are likely to continue to be more pro-poor than urban public investments through the mid-2020s. After the mid-2020s, investments in cities become more pro-poor. The authors show that though rapid economic growth and structural transformation have diminished the relative importance of the agricultural sector in Ethiopia’s economy, continued public investments in agriculture and the broader agrifood system remain crucial for equity and poverty alleviation (and for a reduction of food import dependency) in Ethiopia.